2022
DOI: 10.1093/hmg/ddac228
|View full text |Cite
|
Sign up to set email alerts
|

Non-coding RNAs associated with Prader–Willi syndrome regulate transcription of neurodevelopmental genes in human induced pluripotent stem cells

Abstract: Mutations and aberrant gene expression during cellular differentiation lead to neurodevelopmental disorders, such as Prader-Willi syndrome (PWS) which results from the deletion of an imprinted locus on paternally inherited chromosome 15. We analysed chromatin-associated RNA in human induced pluripotent cells (iPSCs) upon depletion of hybrid small nucleolar long non-coding RNAs (sno-lncRNAs) and 5’ snoRNA capped and polyadenylated long non-coding RNAs (SPA-lncRNAs) transcribed from the locus deleted in PWS. We … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 58 publications
0
9
0
Order By: Relevance
“…This indicated that transcription and splicing of the SNHG14 primary transcript is essentially unaltered during differentiation. We detected previously reported sno-lncRNAs, long ncRNAs containing two SNORD116 snoRNAs joined by a linker (Sledziowska et al ., 2023; Wu et al ., 2016; Yin et al ., 2012). During differentiation, accumulation of sno-lncRNA 1-3 decreased, sno-lncRNA 4 was unchanged, while sno-lncRNA 5 was not detected.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…This indicated that transcription and splicing of the SNHG14 primary transcript is essentially unaltered during differentiation. We detected previously reported sno-lncRNAs, long ncRNAs containing two SNORD116 snoRNAs joined by a linker (Sledziowska et al ., 2023; Wu et al ., 2016; Yin et al ., 2012). During differentiation, accumulation of sno-lncRNA 1-3 decreased, sno-lncRNA 4 was unchanged, while sno-lncRNA 5 was not detected.…”
Section: Discussionmentioning
confidence: 94%
“…This confirmed that transcripts around SNORD115 markedly increased during differentiation, while those around SNORD116 and at sites further 5’ were essentially unchanged. Extended snoRNA-related RNAs SPA1 and sno-lncRNAs 1-4 (Sledziowska et al ., 2023; Wu et al ., 2016; Yin et al ., 2012) were readily detected (Fig. 2B), but showed only modest changes during differentiation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…While it has long been understood that perturbations of the chr15q11-13 region cause PWS, it is unclear if the genes included in the deletions are directly related to PWS phenotypes, if genes regulated by them are to blame, or if it is some combination of these effects. Multiple studies have atempted to address this issue by characterizing gene expression in postmortem PWS brain tissues and neurons differentiated from PWS patient-derived pluripotent stem cell lines to identify genes dysregulated in this disorder (Bochukova et al, 2018; Falaleeva et al, 2015; Huang et al, 2021; Sledziowska et al, 2023; Victor et al, 2021). While these studies indicate gene expression is indeed dysregulated in PWS patient samples, our analysis here showed few genes had consistent dysregulation across a subset of these studies (Supplemental Figure 1A).…”
Section: Discussionmentioning
confidence: 99%
“…Since the function of SNORD116 thus far has remained elusive, much effort has recently been expended to identify gene expression paterns that are dysregulated in PWS. Several studies have compared gene expression between tissue or cell lines derived from PWS patients and those from unrelated controls (Bochukova et al, 2018; Falaleeva et al, 2015; Huang et al, 2021; Sledziowska et al, 2023; Victor et al, 2021). While each of these studies identified numerous genes with distinct expression paterns in the PWS context, a coherent set of consistently dysregulated disease relevant genes has not been identified.…”
Section: Introductionmentioning
confidence: 99%